Knowledge Levels of Anemia Among Female Adolescents: A Descriptive Study - Dewi, Berlian Kusuma; Nurjanah, Suci; Hardi, Gilar Wisnu; Toruan, Sari Artauli Lumban; Winani, Winani; Efendi, Bachtiar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Anemia is one of public health issue affecting female adolescent nationally and globally, particularly in female adolescents. Female adolescent who are experiencing anemia may have serious implication for physical growth, future reproductive health, and cognitive function. Previous studies reveal a lack of knowledge of anemia among this vulnerable population. Therefore, the analysis of knowledge levels related anemia in female adolescents is important to inform effective intervention strategies and prevent further complications. Objective: To investigate the analysis of knowledge related anemia among female adolescents. Method: A cross-sectional approach with purposive sampling and structured questions with validity 0.468 and reliability 0.960. A sum of 105 female adolescents who met the inclusion criteria participated in the study. Results: 53,3% of the female adolescents were found has poor knowledge related anemia with mean age of participants was 16 years old. Conclusion: A proportion of female adolescents exhibit less knowledge related anemia, therefore, it is necessary to develop interactive educational media and health promotion regarding anemia by the school and district health authorities